Estudo da flambagem lateral com torção de vigas de aço de alma senoidal - Heins Hackbarth Junior (2006)
The problems relate to lateral-torsional buckling of doubly and singly symmetric I-shaped steel beams with sinusoidal web have been considered in this paper. ANSYS is used to obtain the critical elastic moment of beams under several types of load. The results are comparedwith the values of two design procedures: (1) the simplified procedure of Zeman, important European manufacturer of steel structural components with sinusoidal web, and; (2) the ANSI/AISC 360-05 procedure for I-shaped beams with flat plate web, adapted to sinusoidal web. This comparison shows that the last procedure can be used to predict the buckling capacity of the sinusoidal web beams made in Brazil with good accuracy and safety.